Revising Public Agricultural Support to Mitigate Climate Change - Searchinger, Timothy D.; Malins, Chris; Dumas, Patrice; Baldock, David; Glauber, Joe; Jayne, Thomas; Huang, Jikun; Marenya, Paswell (Washington, DC: World Bank, 2020)
Agriculture generates roughly one-quarter of global greenhouse gas emissions. By 2050, without major mitigation efforts, agricultural emissions are likely to reach levels that would make meeting global climate targets practically unachievable. Meanwhile, countries that produce two-thirds of the world's agricultural output provided US$600 billion per year in agricultural financial support on average from 2014 to 2016. By evaluating these support programs, both overall and with six case studies, this report finds that many governments have moved to make their farm support less likely to distort what farmers produce, but only a modest portion of programs support environmental objectives, and even fewer support the mitigation of climate change.